Active Control Vibration of a Smart Composite Plate for various Boundary Conditions - Dr.M. Latrache, N.Menasri (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
In this paper, the finite element formulation of the classical laminated plate with embedded piezoelectric patches is based on the first order shear deformation theory (FSDT) and Hamilton’s principle, in this formulation the mass and stiffness of the piezoelectric have been taken into account. The formulation results in a coupled finite element model with mechanical (displacements) and electrical (charges at electrodes) degrees of freedom. The use of the piezoelectric actuator and sensor patches for vibration active control of smart composite plates is discussed. A Linear Quadratic Regulator (LQR) controller is designed based on the independent mode space control techniques to stifle the vibration of the system. Numerical results obtained with the present finite element FE model are found to be in good agreement with ANSYS. The effects of the boundary conditions control vibration of the smart composite plate are examined.